Attrition of materials in fluidized bed - Zhao, Han (2016)
In order to resemble ball milling process which shows better performance in moving heavy metal in incinerator bottom ash (IBA), two sizes of glass beads (0.212-0.6 mm and 0.6-1.0 mm) are utilized to co-fluidize with incinerator bottom ash (IBA) in lab scale fluidized bed at constant gas velocity (1.3 m/s). Current study focuses on the effect of different sizes of glass beads on attrition of IBA, as well as the effect of different compositions of glass beads. The results reveal that both sizes of glass beads enhance the overall attrition rate of IBA, and improve breakage of the largest sized particle. In term of fines, small glass beads will play marginally higher effect on attrition at an initial stage than medium glass beads due to larger contact surface area; however, big glass beads show more attrition at the end of the run possibly due to higher energy per unit area. Additionally, the effects of three gas velocities and hardness on attrition of three materials (activated charcoal, anhydrous gypsum, silicon dioxide) are also investigated. Results show gas velocity has effect on attrition of biggest size range of materials, despite no noticeable effect on attrition of other size ranges has been found. Furthermore, attrition will decrease with increasing the material hardness. In the size of 1.4-1.7mm, attrition of charcoal is vigorous and smooth while the attrition of silicon dioxide and anhydrous gypsum are similar in the beginning and different at later stage. It is due to large formation of subsurface crack in gypsum and little formation in silicon dioxide. Generation of fines will increase with decreasing material hardness. Mechanisms concerning different behaviors are revealed.